Is COVID-19 that different in hemodialysis patients?: A single-center experience - Reis,Marina (2021)
ABSTRACT Coronavirus disease 2019 (COVID-19) has affected millions worldwide, and in particular the care of patients on maintenance hemodialysis. These patients are thought to be at high risk of severe SARS-CoV-2 infection due to their older age and multiple comorbidities. The aim of this study was to compare hemodialysis and non-dialysis COVID-19 patients and find possible risk factors for mortality in hemodialysis patients. We developed a single-center retrospective cohort study, from March 1st to December 31st, 2020, that included maintenance hemodialysis patients hospitalized with laboratory confirmed SARS-CoV-2 infection, and age and sex propensity matched non-dialysis patients also hospitalized with a laboratory confirmed SARS-CoV-2 infection (1:1). A total of 34 hemodialysis patients were included, 70.6% male, mean age 76.5 years and on maintenance hemodialysis for 3.0 [0.5-23] years. At admission, 50.0% needed oxygen supply. Median hospital stay duration was 11.0 [5.8-17.0] days, and 38.2% developed bacterial superinfection. Maintenance hemodialysis patient mortality rate was 32.4%. When matched to the non-dialysis group, the hemodialysis group developed more often respiratory insufficiency (50.0% vs 8.8%, p<0.001) and had higher ferritin (1658.0 vs 623.5, p=0.004) and troponin T (130.0 vs 31.0, p<0.001) levels, whereas the non-dialysis group had higher transaminases levels. There was no statistical difference regarding hospitalization time, bacterial superinfection, or mortality between groups. When the logistic regression was performed, only bacterial superinfection was a predictor for mortality in hemodialysis COVID-19 patients (0.01 [0.00-0.26]). There was no difference in hospital stay nor in death rate between hemodialysis and non-dialysis COVID-19 patients. Despite these results, we must emphasize that mortality in the dialysis group was particularly high, with up to 32% of in-hospital mortality, and that bacterial superinfection has been shown to be an independent predictor of mortality. These results highlight the importance of interventions, such as full vaccination coverage, to mitigate the burden of COVID-19 in hemodialysis patients.